Organized community sport participation for children and youth with physical disability: A scoping review protocol - Karen Davies; Mitchell Barran; Colleen Pawliuk; Tiago Choi; Bruna Schilbach Pizzutto; Karen Lai; Patricia Moreno Grangeiro; Courtney L. Pollock (PLoS ONE, 2026)
Children and youth living with physical disability have less opportunities to participate in organized meaningful physical activities in their communities than their typically developing peers. Equitable access to community sport programs that aim to support the health, social participation, and well-being of these children and youth is required. Frameworks for program implementation and evaluation offer practical tools for supporting quality participation. Limited research exists demonstrating the practical application of these conceptual model frameworks. The objective of this scoping review is to identify evidence of evaluation of organized community sport participation opportunities for children and youth with physical disabilities through the lens of the RE-AIM and Quality Parasport Participation Frameworks. This review will consider studies that explore organized community-based sport participation for children and youth up to 25 years with physical disability without limitation to specific geographic area. Children and youth with only a cognitive or intellectual disability, or the absence of a physical disability, will be excluded. The databases to be searched include MEDLINE (Ovid), Embase (Ovid), SportDiscus (EBSCO), CINAHL (EBSCO), PEDro, Global Index Medicus and Google Scholar. Sources of grey literature will also be searched. Anticipated limitations are the exclusion of clinical intervention trials and the exclusion of unorganized sport. The latter may limit cultural relevance and global scope, as informal sports could dominate in this context and be underrepresented in the literature. Languages will also be restricted to English, French, Portuguese and Spanish. No publication date restrictions will be placed on the search. Two independent reviewers will perform title and abstract screening, and retrieval and assessment of full-text citations. Any disagreements that arise between the reviewers at each stage of the selection process will be resolved through discussion or with a third reviewer. A narrative synthesis of the results will be presented in conjunction with a tabular and/or graphic format.